KEBEBASAN BERPENDAPAT MELALUI MEDIA BARU DALAM BAYANG-BAYANG UU INFORMASI DAN TRANSAKSI ELEKTRONIK (ITE) - Akhmad Syafrudin Syahri (Universitas Bina Sarana Informatika, 2010)
The new technology of information and communications development that will affect to every aspect of human life was already predicted by Alvin Toffler in his ‘The Third Wave’. Democracy as a mainstream ideology that is most followed by countries around the world can’t avoid to this effect. By new technology of information and communications, democracy process become more transparent and dissemination of democracy values go with no limit. The new technology is also creating new alternative media that run on world wide web (www) platform or as known as internet.New media and democracy today have very tight connection. The freedom of speak celebrates through new media. It’s not just the matter of unlimited speaking right, but in the angle of democracy the people voices can be a balance to democracy itself.But sometimes, the policy that issued by the state is not in compliance with the change. To run a state, there were many interests are played. In this article, writer is aimed to describe how democracy component which is the freedom of speak is threatened by a new regulation.This article is arranged by writer’s observation and analysis on some cases that was published in mass media. It’s also based on some academic literatures study, especially in communications studies.The conclusion in the end of the article mentions that the regulation need more improvement that should made by people who have competencies in the field. Self regulation by people who use the new media maybe an alternative of effective way to control the freedom of speaks through new media. Keywords: The freedom of speak, new media, Information and Electronic Transaction Act